Influence of Biological Agents in Controlling Nematodes and Improving Growth of Coffee Seedling and Soil P-Availability - Fitriatin, Betty Natalie; Hindersah, Reginawanti; Asyiah, Iis Nur; Rahayu, Dwi Suci (International Journal of Sustainable Agricultural Research, 2022)
Pests and diseases cause significant yield losses in coffee cultivation in Indonesia. In particular, Pratylenchus coffeae is the most common nematode in Indonesia known to harm coffee plants. In dealing with the threat of P. coffeae, mycorrhiza is used as a biological agent to increase the growth of coffee plants as well as control the nematode. This experiment was conducted to determine the formulation of biological agents in the form of mycorrhizae enriched with mycorrhizal helper bacteria (MHB) to control nematodes and increase the growth of coffee seedlings and soil P-availability. The mycorrhizae used in this experiment were Glomus spp., while the liquid MHB formula used Pseudomonas diminuta and Bacillus subtilis. The randomized block design was used with treatments consisting of control (without biological agents); inoculation of P. coffeae; Glomus + P coffeae; Glomus + MHB 108+ P coffeae; Glomus + MHB 109+ P coffeae. Observations were made on the growth of coffee seedlings and the nematode population of P. coffeae 10 weeks after administered treatments. Results revealed that inoculation of biological agents Glomus spp. + the liquid MHB formula increased the growth of coffee seedlings, soil P-availability, and reduced the population of P. coffeae. The best treatment was Glomus spp. + MHB 108 which can reduce the population of P. coffeae by 65%.